(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The rapid development of information and communication technologies has significantly transformed the educational landscape worldwide. In recent years, digitalization has become a key strategic priority in vocational and technical education, particularly in technical colleges that focus on developing practical skills aligned with labor market demands. This article examines the digitalization of academic processes and the implementation of electronic management systems in technical colleges. Special attention is given to the use of electronic journals, online learning platforms, and digital administrative tools, as well as their impact on improving educational quality, transparency, and efficiency. The study analyzes theoretical foundations of educational digitalization, explores international best practices, and discusses practical challenges and prospects for the effective integration of information technologies in technical colleges. The findings suggest that digital tools not only optimize academic management but also enhance student engagement, teacher performance, and institutional accountability.